Blood‐Compatible Materials: Blood‐Compatible Materials: Vascular Endothelium‐Mimetic Surfaces that Mitigate Multiple Cell‐Material Interactions (Adv. Healthcare Mater. 7/2021). Issue 7 (7th April 2021) - Vlcek, Jessica R.; Hedayati, Mohammadhasan; Melvin, Alyssa C.; Reynolds, Melissa M.; Kipper, Matt J.
Abstract : In article number 2001748 by Matt J. Kipper and co‐workers, nanostructured surfaces that mimic features of the blood vessel wall and that deliver nitric oxide can be tuned to favorably influence cell‐surface interactions with platelets, leukocytes, and bacteria. These surfaces could be used to develop advanced blood‐compatible materials.